Diversity of Plankton Bio-indicators on Water Quality of Lutan Lake, Palangka Raya, Central Kalimantan, Indonesia - Ruthena Yuli; Anggoro Sutrisno; Retnaning Soeprobowati Tri (E3S Web of Conferences, 2023)
Lutan Lake in Palangkaraya is one of the most important oxbow lakes for the people of Palangka Raya. The many water resources with high economic value in Lutan Lake require sustainable management to maintain their quality. One of the indicators for determining lake water quality is the analysis of bio-indicators and water’s physical and chemical quality. The purpose of this study was to analyze the quality of lake water using the presence of biological indicators such as plankton and water quality parameters. This study used a quantitative descriptive method with a survey approach. The sampling was carried out at four stations with two-time variations, i.e., at 04.00 p.m. and 10.00 p.m. Based on the study’s results, it was found that the quality of Lutan lake water for classes I, III, and IV were included in the lightly polluted category. For class II, it was in the moderately polluted category. The plankton parameter shows that the index of phytoplankton and zooplankton diversity looks low with an indication of an unstable aquatic ecosystem due to the dominance of species which indicated the condition of the waters of Lake Luta has been polluted.